Pengembangan Budaya Religius Terhadap Siswa Dalam Peningkatan Mutu Pendidikan Agama Di SMKN 1 Mas-Ubud Gianyar Bali - I Nyoman Sueca (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2020)
The purpose of national education is to make a smart nation and develope a wholly Indonesian people, namely human beings who believe and devote to the Almighty God and have virtuous character, knowledge and skills, physical and spiritual health, a solid and independent personality and responsibility. Hindu religious education becomes guidance to fulfill life and educate society, how should become a good personality, conduct or behave not against dharma or ethics. Efforts to improve the quality of intellectual education, development of religious culture by teachers to the students at Vocational High School I of Ubud is continouesly improved in order to educate and advance Hindus nationally. The development of religious culture towards the Hindu generations is the cultivation of religious values ​​as a personality culture, so that they become virtuous human beings. But the development of the religious culture of the younger generation of Hindus in Vocational High School I of Mas Ubud has not been able to show maximum results if it is seen from attitude and morals. Regarding the social and cultural conditions of students at Vocational High School I Ubud, which are currently ravaging education nowdays, researcher is interested in searching three main problems. 1) What is the process of developing religious culture towards students in improving the quality of religious education in Vocational High School I of Ubud ?; 2) What are the forms of religious culture in improving the quality of religious education in Vocational High School (SMK) I of Ubud ?; 3) What are the implications of religious culture for students related to the improvement of the quality of religious education in Vocational High School (SMK) I of Mas Ubud?, and with three relevant theories namely structural theory, functional stratification theory, and role theory. The hope of the community in developing religious culture for the students as Hindu generation is also mentioned in the scripture of Sarasmuscaya, because the opportunity to be a human being is very important, because being human can improve bad deeds to be good ones. Efforts to understand religious values ​​will influence the positive attitude that must be possessed by every student as a Hindu generation, especially the Hindu as a form of Sradha Bhakti (belief and devotion).